Double network hydrogel–biochar composites with enhanced water absorption and salinity tolerance for sustainable agriculture - Dzureen, Julaihi; Cindy Tan, Soo Yun; Wang, Lin-Chi; Mohamad Izzat Arif, Nordin; Kavirajaa Pandian, Sambasevam; Chin, Suk Fun; Liew, Fui Kiew; Lam, Su Shiung; Peter Yek, Nai Yuh; Margaret, Abat; Nazrizawati, Ahmad Tajuddin (Elsevier Ltd., 2026)
Inefficient irrigation practices in conventional irrigated agriculture contribute significantly to water scarcity, resource wastage and declining soil health. Coupled with accelerating climate change and urbanization, these challenges highlight the urgent need for innovative water retention agents (WRAs) that can boost water absorbency and promote water-use efficiency for sustainable agriculture. Novel double network hydrogel-biochar composites (DNHBCSx) were synthesized by employing a facile one-pot method, integrating covalently-crosslinked potassium poly(acrylate-co-acrylamide) (P(AA-co-AM)), dynamically-crosslinked poly(vinyl alcohol) (PVA) and palm kernel shell biochar (BC). Three key reactants, namely methylene bisacrylamide crosslinker (MBA), PVA and BC loadings, were optimized for equilibrium water absorption (EW) using Response Surface Methodology-Central Composite Design (RSM-CCD) under deionized (DI) water and saline (0.9% w/v NaCl) conditions. The ANOVA confirmed the relevance of the quadratic polynomial model (p < 0.05), revealing PVA, BC and MBA-PVA interaction as dominant factors affecting EW. The optimized formulation, DNHBCS6 exhibited EW of 321.46 g/g in DI water, 34.59 g/g in 0.9% w/v NaCl and 40.94 g/g in 0.9% w/v KCl. The BC-reinforced double network structure imparted controlled swelling behaviour, pH responsiveness, salt-responsive reversible swelling and resistance to cyclic structural fatigue while retaining high water absorbency (EW ≥220 g/g). Soil application tests showed increased water holding capacity in sandy loam from 81.47% to 121.47% and retained 29.33% moisture by DNHBCS6 after 21 days, confirming its effectiveness in coarse-textured soils. Achieving a balanced synergy of EW, structural durability and saline tolerance, DNHBCS6 emerges as a robust WRA for agricultural water-use efficiency, particularly in drought-prone and saline-affected regions.